Simultaneous cardiac and respiratory inhibition during seizure precedes death in the DBA/1 audiogenic mouse model of SUDEP - Schilling, William P. (PLoS One, 2019)
This study was designed to evaluate cardiac and respiratory dysfunction in a mouse model of sudden unexpected death in epilepsy i.e., SUDEP. We simultaneously monitored respiration via plethysmography and the electrocardiogram via telemetry before, during, and after an audiogenic seizure. DBA/1 mice responded to an acoustic stimulus with one or two cycles of circling and jumping before entering a clonic/tonic seizure. This was followed by death unless the mice were resuscitated by mechanical ventilation using room air. During the initial clonic phase, respiration declined and cardiac rhythm is slowed. By the tonic phase, respiration had ceased, atrial P-waves were absent or dissociated from the QRS complex, and heart rate had decreased from 771±11 to 252±16 bpm. Heart rate further deteriorated terminating in asystole unless the mice were resuscitated at the end of the tonic phase which resulted in abrupt recovery of P-waves and a return to normal sinus rhythm, associated with gasping. Interestingly, P-waves were preserved in the mice treated with methylatropine during the pre-ictal period (to block parasympathetic stimulation) and heart rate remained unchanged through the end of the tonic phase (765±8 vs. 748±21 bpm), but as in control, methylatropine treated mice died from respiratory arrest. These results demonstrate that a clonic/tonic seizure in the DBA/1 mouse results in abrupt and simultaneous respiratory and cardiac depression. Although death clearly results from respiratory arrest, our results suggest that seizure activates two central nervous system pathways in this model—one inhibits respiratory drive, whereas the other inhibits cardiac function via vagal efferents. The abrupt and simultaneous recovery of both respiration and cardiac function with mechanical ventilation within an early post-ictal timeframe shows that the vagal discharge can be rapidly terminated. Understanding the central mechanism associated with the abrupt cardiorespiratory dysfunction and equally abrupt recovery may provide clues for therapeutic targets for SUDEP.